Increasing the Labor-Related Costs of Business Transfers and Acquisitions—The Spectre of Per Se Liability for New Owners - William H. DuRoss III (Washington University Law Quarterly, 1989)
This survey begins in Part II with an examination of the 1973 Supreme Court decision in Golden State Bottling Co. v. NLRB,. That decision has served as the touchstone for the rapid expansion of successor liability from the National Labor Relations Act (NLRA) to other federal labor statutes and state law. Part III marks the evolution of successor liability under the NLRA. Part IV chronicles the transfer of liabilities to other federal statutes and state laws, and Part V forecasts liabilities likely to be imposed under other statutes. Part VI describes the evolution of the successorship doctrine into an anticompetitive restraint on business transferability which replaces consideration of managerial prerogative with nearly per se liability. Finally, the last section offers new owners some practical options for avoiding or indemnifying these liabilities, but reluctantly concludes that in most transfers the new owner is now the de jure surety for any of the predecessor's labor-related obligations.
Keywords: Labor laws & legislation